Endothelial Activation and Stress Index Is Associated With Adverse Maternal and Perinatal Outcomes in Preeclampsia - Anna S. Scholz; Annabel Kussner; Michael Elsässer; Thomas Luft; Stephanie Wallwiener; Alexandra von Au (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Endothelial dysfunction represents a key driver in the development of preeclampsia. The Endothelial Activation and Stress Index (EASIX) is a validated predictor of endothelial‐related complications in diverse clinical settings beyond obstetrics. Therefore, we aimed to assess the predictive performance of EASIX for adverse maternal and perinatal outcomes in pregnancies with preeclampsia. Methods This retrospective study analyzed data from 986 patients with preeclampsia who delivered at Heidelberg University Hospital between 2017 and 2022. The primary end points were adverse maternal (death; kidney failure; pulmonary edema; eclampsia; disseminated intravascular coagulation; hemorrhage; cerebrovascular event; and hemolysis, elevated liver enzymes, low platelets syndrome); and perinatal events (death, stillbirth, preterm delivery, placental abruption, respiratory distress syndrome, intraventricular hemorrhage, necrotizing enterocolitis). EASIX was calculated as a product of lactate dehydrogenase and creatinine, both divided by platelet counts. Results Five hundred forty‐two patients were eligible for the analysis. EASIX was significantly elevated in patients with a maternal adverse event (1.41±0.86 versus 0.87±0.5, P<0.0001) or perinatal adverse event (1.05±0.65 versus 0.93±0.59, P=0.046) compared with patients without an adverse event. EASIX was independently associated with adverse maternal (adjusted odds ratio [aOR], 2.90 [2.00–4.19]) and perinatal events (aOR, 2.02 [1.21–3.39]). These associations were emphasized when stratifying for early‐onset preeclampsia. EASIX levels of the highest tertile were associated with the shortest remaining time to delivery (adjusted hazard ratio, 2.10 [1.66–2.66]). Conclusions Our findings underline EASIX as an easily available predictive marker of the risk of maternal and perinatal adverse outcomes in patients with preeclampsia. We propose that EASIX may be useful to stratify the individual risk of adverse events, especially in patients with early‐onset preeclampsia.